2005
DOI: 10.1177/107769900508200407
|View full text |Cite
|
Sign up to set email alerts
|

Within the Boundaries of Politics: News Framing of Sars in China and the United States

Abstract: This research examined news frames in coverage of SARS by newspapers in China and the United States. The assumption was that with the adoption of Western news values and practices, the Chinese press would exhibit news frames similar to those found in Western news. The results showed the presence of economic consequences, responsibility, conflict, leadership, and human-interest news frames in both the U.S. and Chinese newspapers. Depending on the newspaper's country of origin, however, the degree and manner of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
165
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 0 publications
15
165
4
2
Order By: Relevance
“…Leung and Huang (2007) for instance found the news frames on SARS stressing China's institutional mismanagement of the outbreak, bureaucratic obstacles, poor health system and primitive living conditions, thus resulting in an unfavorable representation of China as a negative 'Other'. Regarding the applied methodologies, it is remarkable to notice the dominance of framing studies (see Luther and Zhou, 2004;Tian and Stewart, 2005;Beaudoin, 2007) while so far only a small body of research (see Chiang and Duann, 2007) has analyzed SARS by applying discourse analysis as this article strives to do so. For this purpose, we will draw upon Chouliaraki's theory on the mediation of suffering.…”
Section: Academic Research On Sars and Its Media Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Leung and Huang (2007) for instance found the news frames on SARS stressing China's institutional mismanagement of the outbreak, bureaucratic obstacles, poor health system and primitive living conditions, thus resulting in an unfavorable representation of China as a negative 'Other'. Regarding the applied methodologies, it is remarkable to notice the dominance of framing studies (see Luther and Zhou, 2004;Tian and Stewart, 2005;Beaudoin, 2007) while so far only a small body of research (see Chiang and Duann, 2007) has analyzed SARS by applying discourse analysis as this article strives to do so. For this purpose, we will draw upon Chouliaraki's theory on the mediation of suffering.…”
Section: Academic Research On Sars and Its Media Coveragementioning
confidence: 99%
“…For some scholars (see Luther and Zhou, 2004;Zhang and Fleming, 2005;Zhang, 2006) the outbreak of SARS actually proved to be a unique case study of China, its media culture and policies. Leung and Huang (2007) for instance found the news frames on SARS stressing China's institutional mismanagement of the outbreak, bureaucratic obstacles, poor health system and primitive living conditions, thus resulting in an unfavorable representation of China as a negative 'Other'.…”
Section: Academic Research On Sars and Its Media Coveragementioning
confidence: 99%
“…Wu (Wu, 2006) and Dong et al (Dong et al, 2008) found that this local-global discourse aims to reinforce approval of the nation-state and local government's efforts to manage public health. Similarly, economic consequences, individual responsibility, conflict, leadership and human-interest frames were found in both the USA and Chinese newspaper coverage of SARS (Luther and Zhou, 2005) that praised the Chinese government's response to a public health crisis that originated from the outside.…”
Section: News Media Framing Of Healthmentioning
confidence: 99%
“…On an economic dimension, some scholars tend to consider the Party's strict control has been shaken with recognition of market needs by the press under economic reforms since late 1970s (Luther & Zhou, 2005). After those reforms, media turn to commercial sources for funding, in this way marketization may lead to less forces from the party (Jiang, 2007).…”
Section: Social Level: Political and Economic Approachesmentioning
confidence: 99%